PENINGKATAN KINERJA BERBASIS PADA KOMITMEN ORGANISASI DENGAN STRATEGI DAN INOVASI - Kristianto, Djoko (Universitas Slamet Riyadi, 2007)
Abstract Researcher trying to do research of social area specially related to make-up of organizational affectivity, make-up of organizational affectivity become important because representing one of the target of organization (Nahavandi & Makikzadeh, 1993). Existence of resource human being in organization represents one of the important aspects especially with the organizational affectivity. Important human resource in make-up of organizational affectivity because of investment in conducted human resource by many organizations is by dozens and this matter designate that human resource represents important shares. More and more many good organization of consciousness or unconscious stay in the tight emulation atmosphere. Hence no doubt again that situation in this time more and more to require high flexibility because of speed the happening of change. In face of emulation which more and more to tighten and more and more to have nuance of is make-up of the perform, organization find its improvement by way of improving affectivity from organization. Keywords: Performance, organizational, support strategy and innovation.